Modul Pembelajaran Digital Pemasaran Daring Dengan Penghitung Harga Jual Berbasis Android - Aswar Hanif (Sistem Informasi Akuntansi Kampu Kabupaten Karawang, 2021)
Conventional marketing strategies have to start evolving to digital marketing. With so many technologies and tools on the internet, additional learning is needed to optimize their use in marketing. Knowledge of e-marketing is needed by business people. The 4P marketing concept states that price is one of the most important and most flexible elements, which has a significant influence on consumers' purchasing decisions. It takes consideration and good understanding in determining price. Although there is a lot of information on the internet, one of the problems is that these information are generally scattered and has to be searched. This situation sometimes causes other problems in learning, namely time and convenience. The development of a digital learning module with organized content, with a program to calculate the selling price, is expected to help facilitate the learning process about online marketing. The digital learning module is built for android based devices to achieve high accessibility. This provides convenience and comfort in learning.